Decision-making regulatory framework of the introduction of health technologies at the hospitals in Ukraine - O. Filiniuk; D. Aleshko; М. М. Babenko; K. L. Коsyachenko; R. KAHVECI (The State Expert Center of the Ministry of Health of Ukraine, 2022)
The limited resources of the health care system and the COVID-19 pandemic encourage more rational and cost-effective administrative and clinical decisions. To achieve the best health care within available resources, the introduction of the most efficient technologies should be supported, considering organizational, social and ethical issues. Assessment of health technologies at different levels, namely national/regional and hospital, is becoming increasingly important. Adherence to cost-effective approaches to administrative and clinical decision-making will ensure the rational use of the state budget and improve clinical outcomes, improve the quality and life expectancy of patients. The purpose of the study was to analyze the current regulatory framework for the introduction of health technologies (medicines and medical devices) at the hospital level. During the research the methods of content analysis, historical, system-analytical, generalization was used. According to the analysis of the decision-making regulatory framework for the health technology's introduction, it was drawn the next conclusions. The active HTA development in Ukraine is noted. In a short time, a legal framework for state HTA for medicines was created and approved, amendments were made to the Law of Ukraine 'On Public Procurement' and other Ukraine's laws on medicine procurement under managed entry agreements, the further steps for development of the HTA ecosystem in Ukraine were identified. The legal framework for the circulation of medical devices needs to be updated in Ukraine, starting with technical regulations in accordance with EU regulations №745 and №746 and further approval of the Law on Medical Devices. Procedures for evaluation and selection of medicines and medical devices at the level of medical institutions are absent in Ukraine and require separate elaboration. The introduction of HB-HTA will help hospital managers to make independent, transparent, reasonable, and impartial management decisions on the selection of drugs and medical devices. The obtained results prove the need for further research of everyday decision-making practices on the introduction of health technologies at the hospitals, development of methodology for hospital-based HTA and update regulation of HB-HTA in the current legal framework of Ukraine.